Pemahaman Siswa Terhadap Variasi Logat Dalam Bahasa Inggris Di MAN Binjai - Mariana Mariana; Rudi Purwana (Lembaga Pengembangan Kinerja Dosen, 2021)
This research explores students' understanding of English dialect variations at MAN Binjai in 2021. It addresses the urgency of comprehending dialect variations within the globalized education context and the imperative need for English language proficiency in the healthcare domain. Employing a qualitative approach with a case study design, the study involves X and XI grade students selected through purposive sampling. Data collection includes interviews, observations, and document analysis, analyzed thematically. Findings reveal diverse student understandings influenced by religious norms, media, and challenges in adapting to remote learning during the pandemic. The implications highlight contributions to understanding student comprehension variability and formulating adaptive learning strategies in a madrasah setting.